Murcott seedless: influence of gamma irradiation on citrus production and fruit quality - Bermejo, Almudena; Pardo, José; Cano, Antonio (2017)
Seedlessness is an important economic trait relating to fruit quality, and gamma irradiation is a common technique used to obtain seedless citrus fruits. Herein, we report a study of new seedless ‘Murcott’ mandarin clones obtained by bud irradiation from the self-compatible not parthenocarpic ‘Murcott’ mandarin. All irradiated clones examined presented lower seed numbers (from 0.23 to 2.47 seeds per fruit) and reduced pollen germination (from 1.40% to 8.55%) whereas the wild-type ‘Murcott’ showed an average number of 9.03 seeds per fruit and a pollen germination value of 47.15%. Fruit quality and nutritional bio-components were affected differently; some clones presented no changes compared to the control ‘Murcott’ mandarin, while other clones showed significant differences. High-performance liquid chromatographic methods were used to identify and quantify of these compounds, using photodiode array, mass and refractive index detectors. Our results indicated high contents in natural antioxidants as vitamin C (from 20.13 to 25.73 mg/100 mL) and phenolic compounds, as flavonoids, in these citrus varieties cultived under the Mediterranean climate. Some of these clones, which ripen late in the season and whose fruit quality is maintained or improved, are in the process of registration. In conclusion, budwood irradiation is a suitable technique to improve cultivars, produce seedless cultivars, adjust ripening time or raise the content of health-promoting compounds. Also this study investigates the influence of temperature during flowering on the number of seeds formed. Findings indicate that low temperatures during flower formation decreased pollen germination and seed number.